Calculated Molecular Structures Of Anion Ubiquinone In The Gas Phase, In Solvents And In The Qa Binding Site Of Purple Bacteria Reaction Centers - Lamichhane, Hari Prasad (Himalayan Physics, 2012)
Structural properties of ubiquinone one anion radical (UQ1-) are studied in the gas phase and in QA binding site of purple bacteria reaction center using Gaussian 03. Polarizable continuum model (PCM) and Our own N-layered quantum mechanics + molecular mechanics (ONIOM) methods have been used to optimize the UQ1- molecule in solvent and in the QA binding site of purple bacteria Rhodobactor sphaeroides reaction centers. The UQ1- molecule exist four equivalent conformations of methoxy groups in the gas phase and solvents. However, all four conformations reduce to one in the QA binding site of the purple bacteria reaction centers. Both carbonyl (C=O) bond lengths are similar in all four conformations in the gas phase and in solvents. However, C4=O bond is slightly longer than C1=O bond in the QA binding site. This result infers that QA binding site impacts asymmetric interaction on the carbonyl groups of the quinone molecule. The Himalayan Physics Vol. 3, No. 3 2012 Page : 18-23